How forgiveness promotes offender pro‐relational intentions: The mediating role of offender gratitude. (6th July 2015) - Mooney, Louise; Strelan, Peter; McKee, Ian
Abstract : Although relationship restoration is an important outcome of forgiveness, little is known about how forgiveness facilitates such an outcome. In addition, in forgiveness research, little attention is paid to the perspective of the offender. We address these two shortcomings simultaneously, testing the idea that forgiveness promotes offender gratitude, which in turn encourages offender pro‐relational intentions. Across three experimental studies, participants were induced to believe they had transgressed; recalled a time when they had transgressed; and imagined transgressing. In studies 1 and 2, forgiveness was manipulated; in Study 3, victim motivation for forgiving was manipulated. State gratitude – in comparison with guilt, indebtedness, and positive affect – was consistently found to play the primary mediating role between forgiveness and pro‐relational intentions.